2022
DOI: 10.3233/jad-215324
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Insomnia and Sleep Disturbances and the Impact of Sleep Treatments in Patients with Probable or Possible Alzheimer’s Disease: A Structured Literature Review

Abstract: Background: Sleep disturbances are frequent in Alzheimer’s disease (AD). This review summarizes the impact of sleep disturbances on AD patients and their caregivers and the effects of currently available sleep therapies. Methods: Published studies (January 1985–March 2020) assessing the burden associated with insomnia/sleep disturbances in the AD population and insomnia treatment effects were identified by searching PubMed, Embase and Cochrane Library and screened against inclusion criteria. Findings: This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 92 publications
0
11
0
Order By: Relevance
“…For example, Kishi et al [15], Nakamura and Nagamine [24], and Ueda [16] have reported the clinical usefulness of suvorexant in insomnia patients with various psychiatric comorbidities, including depressive disorders, bipolar disorders, neurocognitive disorders (dementia), and schizophrenia spectrum disorders. It is well known that sleep disturbances impose a huge burden on patients with neurocognitive disorders such as Alzheimer's disease [25]. Randomized clinical trials have examined the role of suvorexant in patients with Alzheimer's disease and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kishi et al [15], Nakamura and Nagamine [24], and Ueda [16] have reported the clinical usefulness of suvorexant in insomnia patients with various psychiatric comorbidities, including depressive disorders, bipolar disorders, neurocognitive disorders (dementia), and schizophrenia spectrum disorders. It is well known that sleep disturbances impose a huge burden on patients with neurocognitive disorders such as Alzheimer's disease [25]. Randomized clinical trials have examined the role of suvorexant in patients with Alzheimer's disease and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in a large populational study, sleep disturbances are strongly linked with faster cognitive decline [ 90 ] and the development of dementia [ 91 ]. Indeed, more than 50% of AD patients are affected by sleeping disorders [ 92 ]. In connection with that, both clinical and experimental findings demonstrate that the extracellular levels of AD-associated proteins are modulated by sleep [ 93 , 94 ].…”
Section: The Glymphatic and Meningeal Lymphatic Systems In The Pathop...mentioning
confidence: 99%
“…PwD frequently present with difficulties in falling asleep (58), fragmented sleep (59), and excessive sleepiness during daytime (60). The sleep-wake disturbance in PwD leads to a progressive deterioration of circadian rhythm (61) and, in advanced stages of dementia, even to a reversal of the day-night sleep pattern (58). Sleep disturbance in PwD has been associated with the presence of other NPS such as anxiety and hyperactivity (62).…”
Section: Sleep Problems (Insomnia Excessive Daytime Sleepiness)mentioning
confidence: 99%